PERAN PERBANKAN SYARIAH TERHADAP BAZNAS KOTA BEKASI - Annie Faridha Farachdina; Isfandayani Isfandayani; Siti Mardiah (LPPM Universitas Islam 45, 2022)
Zakat has a goal to improve the economic welfare of mustahiq. BAZNAS (National Amil Zakat Agency) is an institution for the collection and distribution of zakat owned by the Indonesian government. The presence of Islamic banking is expected to be able to play a role in realizing the goals of zakat and BAZNAS programs. This study discusses the role of Islamic Banking in Bekasi City BAZNAS. The research used is qualitative with primary and secondary data. The data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the Islamic banks that have collaborated with BAZNAS Bekasi City are BTN Syariah, BJB Syariah, and Mega Syariah, with several cooperation programs. The role of Islamic Banking in Bekasi City BAZNAS using Maqashid Syariah analysis has been achieved, but in terms of funding it has not been optimal.